CYBERSECURITY WITHIN CYBERSPACE - Čapek, Jan; Holá, Jana (Trauner Verlag, 2016)
Introduction of computers in all spheres of life substantially changed the ways of how people communicate and exchange information. It is creating a virtually paperless work environment. Also we can now send a message very easily to anywhere in the world in seconds. Internet and its penetration into the so-called cyberspace puts users at cyber space requirements for information security, ICT security and, finally, cyber security for survival in this cyber space. Most countries in the world developing their own centres dealing with cyber security such as a national security authority, the approach of Czech Republic will be discussed.
Kybernetická bezpečnost uvnitř kybernetického prostoru
Keywords: Cyberspace; Information security; Cyber security; ICT; National Security Authority; Kybernetický prostor; Informační bezpečnost; kybernetická bezpečnost; ICT; Národní bezpečnostní autorita